Study on Laser Assisted Micro Milling (LAMM) Processing C haracteristic of Titanium Alloy (Ti6Al4V) using TiAlN coated carbide micro ball mill - Abd. Rahim, Erween; Ismail, Mohd. Idris Shah; Ibrahim, Mohd. Rasidi; Mohid, Zazuli; Md. Warap, Norazlan (9th International Conference on MicroManufacturing (ICOMM 2014), 2014)
Machining of hard-to-machine materials requires excellent cutting tool performance in terms of tool wear and life. By integrating other process such as laser as a pre-heating element in machining process, cutting force can be effectively reduced. However, applying heat from external source promotes of other defects. In addition, the microstructure of sub-surface layer prone to alter. As a result, an appropriate combination of heating temperature and machining parameters need to be determined. In this study, the heating temperature characteristics were determined numerically and validated by observing the heat affected zone (HAZ) and melted zone (MZ) obtained from experiment. The tool location and machining parameters were also determined by referring to the three dimensional temperature distribution obtained from numerical analysis. The laser heating was successfully decreased the thrust forces under certain depth of cut. The formation of melted zone and heat affected zone created by pulse wave laser significantly influence the LAMM processing characteristics.
Keywords: Laser Assisted Micro Milling (LAMM); Finite Element Analysis; Titanium Alloy; Nd:YAG Laser